Academic Anxiety Among Specially-Abled Secondary School Students With Special Reference To Gender And Type Of Disability. - Sultan Rather, Mohd; Iqbal Mattoo, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Children with special needs are vital contributors of society, showcasing excellence despite their disabilities. To ensure their growth and progress it’s essential to offer prompt attention, nurturing education and research in this field. Keeping this in mind, the present research was conducted on 100specially-abled secondary school students and the study shows that different people experience different levels of academic anxiety and that gender has no bearing on it. The present study explores academicanxiety among students with special needs and its adverse effects on their wellbeing. By combining existing literature and effective methodologies, it offers insights to create an inclusive educational environment for all high school students, including those with special needs. it provides valuable insights for educators, parents, and policymakers in creating an inclusive and supportive educational environment